Differential prognostic association of systemic inflammatory biomarkers on survival outcomes in head and neck squamous cell carcinoma patients by human papillomavirus status - Pardis Noormohammadpour; Katrina Hueniken; Martha Pienkowski; Shao Hui Huang; Baijiang Yuan; Benjamin Grant; Christopher Yao; Andrew Hope; Jillian Tsai; Andrew McPartlin; David Goldstein; Ali Hosni; et al. (Neoplasia: An International Journal for Oncology Research)
Systemic inflammatory response (SIR) markers are prognostic in various cancers. In a prospective cohort study (2006-2019) involving 2044 head and neck squamous cell carcinomas (HNSCC) patients, we assessed the prognostic associations of SIR markers at diagnosis, including NLR (neutrophil-to-lymphocyte ratio), PLR (platelet-to-lymphocyte ratio), LMR (lymphocyte-to-monocyte ratio), NMR (neutrophil-to-monocyte ratio), SII (systemic immune-inflammation index), eosinophil and WBC (white blood cell) levels, with progression-free (PFS) and overall survival (OS). Training (two-thirds randomly selected patients) and withheld test sets were created. Separate multivariable Cox regression models by HPV status were created for each of the seven SIR markers for the training set, and validated in the withheld test set. We found that the majority of SIR markers are strongly and significantly associated with OS and PFS in HPV-positive HNSCC patients, while the results were less significant or of lesser magnitude of association in the HPV-negative HNSCC patients. Despite validating these prognostic associations, the addition of SIR markers to a clinical prognostic model did not significantly improve predictive performance for PFS/OS. Our study demonstrates that SIR markers may have a greater impact on the survival of HPV-positive HNSCC, and less so for HPV-negative HNSCCs. These results suggest differential prognostic impact of inflammation between HPV-driven HNSCCs and non-HPV-driven HNSCCs. Although biologically relevant, these associations do not improve survival prognostication in the clinical setting.